The Practice of Occult Theology - Purwoko Agung Nugroho (Journal of Social Science, 2022)
The practice of Occultism knows no place and time. Even though the world has undergone radical changes marked by advances in science and technology, there are still people who want to practice Occultism. Many of these occult practices are generally inherited from their ancestors and passed down from generation to generation until now. Many Christians carry out Occult actions for various reasons, such as fear of ancestral spirits, not being protected by them, or feeling that ancestral spirits do not bless them. Occult practices are actions that are far from Christian truth. The occult does exist on this earth. The purpose of this study is to analyze the current occult practice. The method used is qualitative research in the form of library research method. Therefore, a believer must be vigilant and on guard to avoid this occult practice.